ANALISIS TERHADAP PERATURAN PEMERINTAH NO 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK DITINJAUDARI PRINSIP NON DISKRIMINASI DALAM KONVENSI HAK ANAK (CONTOH KASUS POLWAN GAGAL ADOPSI ANAK KARENA TERHALANG PERATURAN PEMERINTAH) - Stanley Noer H; Mulati . (Fakultas Hukum Universitas Tarumanagara, 2018)
Child is a gift from God Almighty, who inherent in dignity and dignity as a whole person. Children also have human rights recognized by the nation-states in the world. Children's rights are marked by the guarantee of protection and fulfillment of the Rights of the Child in the 1945 Constitution of the State of the Republic of Indonesia and several provisions of laws and regulations both national and international. This guarantee is upheld through the ratification of the International Convention on the Rights of the Child, namely the ratification of the Convention on the Rights of the Child through Presidential Decree No. 36/1990 on the Ratification of Convention On The Rights Of The Child. In the case that the authors found that there was an adoption of a child who could not be made due to Government Regulation No. 54 of 2007 article 3, paragraph 2 stating that in the case of the origin of the child is unknown, the child's religion is in accordance with the religion of the majority of the local population. With this case, according to the author means there has been discrimination against prospective parents who have good intentions to appoint children because of the constraints of religious differences between parents and prospective children. Whereas in the course of the child is also possible to choose a different religion with the parents' religion. Directly this Government Regulation is contrary to the principle of Non-Discrimination adopted by the Convention on the Rights of the Child